Clinicoradiological Manifestations of Melioidosis with Pulmonary Involvement in a Tertiary Hospital Setup - P Prem Ananth; R Anand; R Prathipa; S Raghul Raj; N Nagarajan (Journal of Association of Pulmonologist of Tamil Nadu)
Background: Melioidosis, caused by the Gram-negative bacterium Burkholderia pseudomallei, can have varied presentations ranging from acute, subacute, or chronic presentation. Our study aims to comprehensively investigate and analyze the epidemiology and clinicoradiological characteristics of melioidosis along with their prognosis. Materials and Methods: This was a single-centered retrospective observational study where the data of 30 culture-positive melioidosis patients admitted to our hospital from August 2020 to August 2023 were collected and analyzed. All the patients were subjected to routine chest X-rays or high-resolution computed tomography thorax during admission. Results: The median age was 45.6 (41–60 years). Males were more commonly affected than females. Diabetes mellitus was the most common comorbid followed by chronic kidney disease. Radiologically, the right upper lobes (46.6%) are more commonly involved followed by the left upper lobe (23.3%). Systemic involvement of melioidosis shows isolated pulmonary (Lung plus Pleura) involvement at up to 38% followed by disseminated melioidosis at 33% (more than two or more organs involved), with liver and lymph nodes both accounting for 9%. The most common pulmonary presentation was a cavity (50%), followed by lobar infiltrates (46.6%) and atelectasis (33.3%). Around 10 patients had a chronic presentation with bone and joint involvement (6.6%), lymphadenopathy (10%), and pleural empyema (16.6%). The delay in diagnosis in these chronic cases is attributed to their atypical presentation often mimicking tuberculosis or malignancy. Among the 30 patients, 22 patients improved with treatment, seven patients went against medical advice, and one patient succumbed to the disease. Conclusion: Our study highlights the importance of clinical assessment, radiological findings, appropriate sampling, and culture methods in suspected melioidosis cases, especially in patients residing in endemic areas such as the coastal areas of Tamil Nadu, thereby initiating early antibiotics for improved patient outcomes.